Inferred rheological structure and mantle conditions from postseismic deformation following the 2010 Mw 7.2 El Mayor-Cucapah Earthquake. Issue 3 (18th December 2017) - Dickinson-Lovell, Haylee; Huang, Mong-Han; Freed, Andrew M; Fielding, Eric; Bürgmann, Roland; Andronicos, Christopher
SUMMARY: The 2010 M w 7.2 El Mayor-Cucapah earthquake provides a unique target of postseismic study as deformation extends across several distinct geological provinces, including the cold Mesozoic arc crust of the Peninsular Ranges and newly formed, hot, extending lithosphere within the Salton Trough. We use five years of global positioning system measurements to invert for afterslip and constrain a 3-D finite-element model that simulates viscoelastic relaxation. We find that afterslip cannot readily explain far-field displacements (more than 50 km from the epicentre). These displacements are best explained by viscoelastic relaxation of a horizontally and vertically heterogeneous lower crust and upper mantle. Lower viscosities beneath the Salton Trough compared to the Peninsular Ranges and other surrounding regions are consistent with inferred differences in the respective geotherms. Our inferred viscosity structure suggests that the depth of the Lithosphere/Asthenosphere Boundary (LAB) is ∼65 km below the Peninsular Ranges and ∼32 km beneath the Salton Trough. These depths are shallower than the corresponding seismic LAB. This suggests that the onset of partial melting in peridotite may control the depth to the base of the mechanical lithosphere. In contrast, the seismic LAB may correspond to an increase in the partial melt percentage associated with the change from a conductive to an adiabatic geotherm.